(untitled) (Journal of Health, Population and Nutrition, 2013)
Presentation of pulmonary tuberculosis (PTB) as acute pneumonia in severely-malnourished and HIVpositive children has received very little attention, although this is very important in the management of pneumonia in children living in communities where TB is highly endemic. Our aim was to identify confirmed TB in children with acute pneumonia and HIV infection and/or severe acute malnutrition (SAM) (weight-for-length/height or weight-for-age z score <-3 of the WHO median, or presence of nutritional oedema). We conducted a literature search, using PubMed and Web of Science in April 2013 for the period from January 1974 through April 2013. We included only those studies that reported confirmed TB identified by acid fast bacilli (AFB) through smear microscopy, or by culture-positive specimens from children with acute pneumonia and SAM and/or HIV infection. The specimens were collected either from induced sputum (IS), or gastric lavage (GL), or broncho-alveolar lavage (BAL), or percutaneous lung aspirates (LA). Pneumonia was defined as the radiological evidence of lobar or patchy consolidation and/or clinical evidence of severe/ very severe pneumonia according to the WHO criteria of acute respiratory infection. A total of 17 studies met our search criteria but 6 were relevant for our review. Eleven studies were excluded as those did not assess the HIV status of the children or specify the nutritional status of the children with acute pneumonia and TB. We identified only 747 under-five children from the six relevant studies that determined a tubercular aetiology of acute pneumonia in children with SAM and/or positive HIV status. Three studies were reported from South Africa and one each from the Gambia, Ethiopia, and Thailand where 610, 90, 35, and 12 children were enrolled and 64 (10%), 23 (26%), 5 (14%), and 1 (8%) children were identified with active TB respectively, with a total of 93 (12%) children with active TB. Among 610 HIV-infected children in three studies from South Africa and 137 SAM children from other studies, 64 (10%) and 29 (21%) isolates of M. tuberculosis were identified respectively. Children from South Africa were infected with HIV without specification of their nutritional status whereas children from other countries had SAM but without indication of their HIV status. Our review of the existing data suggests that pulmonary tuberculosis may be more common than it is generally suspected in children with acute pneumonia and SAM, or HIV infection. Because of the scarcity of data, there is an urgent need to investigate PTB as one of the potential aetiologies of acute pneumonia in these children in a carefully-conducted larger study, especially outside Africa. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16516 J HEALTH POPUL NUTR 2013 Sep; 31(3): 308-313